Pulmonary Hypertension in Idiopathic Pulmonary Fibrosis - I. Enghelmayer, Juan; Papucci, Tulio; Raimondi, Alejandro (Clinical Anti-Inflammatory & Anti-Allergy Drugs (Discontinued), 2014)
Idiopathic pulmonary fibrosis (IPF) is a diffuse progressive parenchymal disease. Patients with IPF have a poor prognosis and frequently suffer from pulmonary hypertension (PH) complications, which are associated to significantly worse outcomes. In IPF, the pathogenesis of PH varies and has not been completely understood yet, since it may arise from multiple factors. In these patients, PH is associated with reduced exercise capacity and lower survival rate. Due to its prognostic significance, it would be useful to conduct further research into PH in IPF patients. Though right heart catheterization continues to be the gold standard diagnostic test, the first steps to properly diagnose PH are clinical suspicion (based on increased shortness of breath and reduced diffusing capacity) and echocardiography. The options to treat PH in this population are limited. What is more, to date, there are no approved therapies specifically aimed at PH in IPF patients.
Keywords: idiopathic pulmonary fibrosis